EVALUATION OF STRESS AND ITS INFLUENCE ON QUALITY OF LIFE IN POSTMENOPAUSAL WOMEN - B, Jayabharathi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Background: Menopause is a stage in life when a woman stops having her monthly period. It is a normal part of aging and marks the end of a woman's reproductive years. The age of menopause varies from 45 to 50 years. In some woman, the age of menopause may be 51 or 52 years. Aim: This study aims to evaluate the stress and its influence on quality of life (QOL) in postmenopausal women in selected areas, Kattankulathur Block, Chennai, Tamil Nadu, India. Methods: A cross-sectional study was conducted in selected areas in Kattankulathur Block, Chennai, Tamil Nadu. After initial screening, simple random sampling technique was adopted to select the study participants. The total sample size comprised 130 postmenopausal women. Assessments were made by Sheldon Cohen's, the Perceived Stress Scale for assessing the stress level of postmenopausal women and the World Health Organization QOL-BREF Scale for assessing their QOL. Results: This study showed that the majority of postmenopausal women 90 (70.4%) had very high level of stress. Maximum of postmenopausal women 56 (44%) had very poor QOL, and 59 (46%) were very dissatisfied about their health status. The lower mean scores were found in physical, psychological, social, and environment domain among postmenopausal women. There was moderate negative correlation found between stress and QOL among postmenopausal women. It shows that, when the stress was increased, poor QOL was experienced by postmenopausal women. Conclusion: This study results showed that the majority of postmenopausal women 90 (70.4%) had very high level of stress which negatively affected the QOL of postmenopausal women. Keywords: Stress, Quality of life, Postmenopausal women.